Alternative therapies for sinusitis and rhinitis: a systematic review utilizing a modified Delphi method. Issue 4 (27th February 2020) - Wu, Arthur W.; Gettelfinger, John D.; Ting, Jonathan Y.; Mort, Claudia; Higgins, Thomas S.
Abstract : Background: Sinusitis and rhinitis are common diseases for which patients seek medical attention. Alternative therapies constitute a multibillion‐dollar industry despite poorly established efficacy and safety profiles. This study was designed to identify and grade the evidence for alternative therapies purported to treat sinusitis and rhinitis. Methods: A modified Delphi method was used to establish a consensus opinion among rhinology experts of the current evidence for efficacy, potential harm, and future research needs for alternative therapies in sinusitis and rhinitis. Following the initial Delphi round of discussion, a Google search query was performed to identify topics and review online reports of benefit. Subsequent rounds established search criteria and inclusion/exclusion criteria for a systematic literature review utilizing PubMed, EMBASE, and Cochrane databases. Centre for Evidence‐Based Medicine (CEBM) and Grading of Recommendations, Assessment, Development and Evaluations (GRADE) criteria were used to assess levels of evidence and recommendations. Final Delphi rounds were performed until consensus opinions could be reached. Results: Over 60 potential alternative therapies for sinusitis and rhinitis were identified. The literature review included 2066 titles with 220 full‐text articles found to be relevant. Most of the therapies had little to no scientific evidence; however, acupuncture, capsaicin, bromelain, and butterbur extract currently have low to moderate‐high GRADE rating. Allergic rhinitis was the most common disease studied. Conclusion: Some alternative therapies show promise as potential treatments for sinusitis and rhinitis, mostly compared to placebo. Comparisons to traditional therapies are lacking. For other alternative therapies, many websites included unsubstantiated claims of benefit and ignored potential side effects for which patients should be warned appropriately.